Reshaping Oedipal Myth in the Baahubali Series - Wagle, Anupa (The Outlook: Journal of English Studies, 2026)
Myths are a timeless tool for preserving a community ̓s collective past, as they transmit shared beliefs and traditions across generations. Cinema, as a form of popular culture, plays a crucial role in transmitting, transforming, and revitalizing myth for contemporary audiences. In such context, this article aims to analyze how the Baahubali Series as a cultural text, reshapes the Oedipal myth. Using an interpretive method of textual analysis, the article focuses on elements such as father- son conflict, maternal attachment, and sibling rivalry framed within the ethical dimensions of duty and morality. It also uses shots from the selected movies for thematic interpretation. This article argues that the Baahubali Series reshapes the core tensions- parental authority, sibling rivalry, maternal attachment, and struggle for legitimacy within an ethical context that demands duty, sacrifice, and moral righteousness rather than reproducing the Oedipal complex in conventional Western form. The finding of this article shows that the Baahubali Series directed by S. S. Rajamouli, is replete with Oedipal fixation grounded in the cultural context of dharma, duty, legitimacy, and ethics towards the community rather than the individual psyches of the characters. The significance of this article lies in its analysis of cinema ̓s role in communicating mythologies across generations. This article concludes that the Baahubali series reshapes the Oedipal myth within an ethical context that demands duty, sacrifice, and moral righteousness, rather than reproducing the Freudian Oedipal complex in its conventional Western form. Further, the Baahubali Series has affirmed cinema ̓s role as a popular medium for reshaping ancient myths and preserving mythology and culture through a cinematic lens.